KETELADANAN GURU DAN IMPLIKASINYA TERHADAP KECERDASAN EMOSIONAL SISWA MIN MEULABOH ACEH BARAT - Rafnidar Rafnidar (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2020)
As an educator, a teacher plays an important role in determining teaching and learning success. Educating does not merely a requirement to administrative procedures, but it also involves a totality in its implementation. This means that the whole components of learning are included when educating. Also, being a role model is part of the teacher’s intelligence, attitudes, and behaviors when they need to shape student’s moral, spiritual, and social characteristics. This study examined the issues of the actualization of teachers’ role modeling of MIN (Islamic elementary school) Meulaboh that influenced students’ emotional intelligence, the effects of role modeling that were shown during teacher-student interactions, and the obstacles and the solutions to the development of students’ behaviors relevant to their emotional intelligence. This study was a qualitative study. The data obtained were primary and secondary data. The participants of the study included the principal, vice principal of curriculum affairs, staff of student affairs, administration staff, teachers, and students of MIN Meulaboh, Aceh Barat district. Data were obtained by observation, interview, and documentation. The data were then analyzed through three systematical stages; reduction, display, and verification. Findings showed that teachers’ role modeling could increase students’ emotional intelligence, and gave relevant impact towards the students. It was shown from the increasing harmonious relationship among the students, and also better attitudes such as being polite and reserved, greeting each other, having proper behaviors to one another, and being punctual and discipline. It is hoped that the study would provide valuable contribution to teachers, students, and school itself, and also the findings could provide information on teachers as role models that can influence students’ emotional intelligence, to which further becomes a basis for developing a polite, discipline, and friendly future generation.